PENINGKATAN DAYA SAING PRODUK GULA AREN KEMASAN MELALUI PENGHITUNGAN HARGA POKOK PRODUKSI PADA UKM MUTIARA MERAH PUPUAN TABANAN - Dewi, I.A. L.; Kusmiyarti, T. B.; Pradnyawathi, N. L.; Wrasiati, L. P. (Buletin Udayana Mengabdi; Vol 20 No 4 (2021): Buletin Udayana Mengabdi, 2022)
This mentoring activity aims to improve the skills of KUB Mutiara Merah, Pupuan District, Tabanan Regency in determining the selling price of cylindrical palm sugar. Methods for implementing activities in the form of training and mentoring include simple business bookkeeping, calculating the cost of producing sugar cylinders per production period, and controlling production costs. The results of the activity showed that 100% of partner members participated in outreach activities and in that activity 50% of partner members understood the importance of improving product molds to increase competitiveness, 40% understood the importance of product packaging. In the training activity, 50% of the participants were skilled in implementing the SOP for sugar production with a new type of mold (introduction), and as many as 10% were able to calculate the cost of production. Cost of production Rp. 8,139 per pcs, while the selling price is Rp. 10,000 per pcs so there is a profit margin of IDR 1,861 per pcs. The profit of 4000 pcs cylindrical palm sugar is Rp. 7,444,000,-.  Keywords: Cost of production, selling price, increased sales, competitiveness